2021
DOI: 10.1111/ijcp.14549
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of shoulder calcific tendinopathy in diabetes mellitus: A nationwide, population‐based, matched cohort study

Abstract: Background: Calcific tendinopathy of the rotator cuff is a common cause of painful disability in the shoulder with unclear aetiology. Diabetes mellitus (DM) is associated with calcific tendinopathy; however, large epidemiological data are lacking. Thus, we conducted a nationwide population-based matched cohort study to investigate the risk for calcific tendinopathy of the shoulder in diabetic patients. Methods: The National Health Insurance Research Database of Taiwan was used to include 42 915 patients newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A national population study by Su et al confirmed that the risk of secondary calcific tendonitis in patients diagnosed with either type 1 or type 2 diabetes was about 27%. Their hypothesis for this was that diabetes-induced vascular compromise and hyperglycemic exposure; the former may reduce the supply of nutrients and oxygen to connective tissue, thus causing degeneration and promoting calcification deposits, and the latter may lead to glycosylation of extracellular proteins, thus altering the biomechanical environment and possibly promoting calcification of connective tissue [ 30 ]. Furthermore, distinguishing between symptomatic and asymptomatic RCCT, after searching the literature, we found that Siu et al reported elevated subacromial fluid IL-1 β levels in diabetic patients with shoulder pain and shoulder stiffness, which may be strong evidence to support the diagnosis of symptomatic RCCT [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A national population study by Su et al confirmed that the risk of secondary calcific tendonitis in patients diagnosed with either type 1 or type 2 diabetes was about 27%. Their hypothesis for this was that diabetes-induced vascular compromise and hyperglycemic exposure; the former may reduce the supply of nutrients and oxygen to connective tissue, thus causing degeneration and promoting calcification deposits, and the latter may lead to glycosylation of extracellular proteins, thus altering the biomechanical environment and possibly promoting calcification of connective tissue [ 30 ]. Furthermore, distinguishing between symptomatic and asymptomatic RCCT, after searching the literature, we found that Siu et al reported elevated subacromial fluid IL-1 β levels in diabetic patients with shoulder pain and shoulder stiffness, which may be strong evidence to support the diagnosis of symptomatic RCCT [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, diabetes mellitus is a major factor affecting tendon quality and leading to tendinopathy ( 2 ). In recent years, the increasing number of people with diabetes has prompted a large number of studies ( 3 , 4 ) to focus on the adverse effects of diabetes on tendons. Some studies have shown that diabetes alters the physical and chemical properties of tendons and the arrangement of collagen fibers, extracellular matrix composition, and biomechanics in a high-glucose microenvironment ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic tendinopathy is a common disease of the musculoskeletal system in patients with diabetes mellitus (DM) (Giha et al 2022;Cai et al 2018) that causes chronic pain, movement restriction, tendon micro-damage and rupture, and seriously affects patients' quality of life (Lui 2017; Mavrikakis et al 1989). Calci c tendinopathy is a serious type of diabetic tendinopathy (Su et al 2021;Lu et al 2020)mainly caused by calcium deposition in tendons, aggravating the clinical manifestations of diabetic tendinopathy (Oliva et al 2012). Currently, effective means of clinical prevention and treatment of calci c tendinopathy are limited because the pathogenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%